2021
DOI: 10.3389/fnins.2021.767302
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Auricular Vagus Nerve Stimulation (tAVNS) Delivered During Upper Limb Interactive Robotic Training Demonstrates Novel Antagonist Control for Reaching Movements Following Stroke

Abstract: Implanted vagus nerve stimulation (VNS) delivered concurrently with upper limb rehabilitation has been shown to improve arm function after stroke. Transcutaneous auricular VNS (taVNS) offers a non-invasive alternative to implanted VNS and may provide similar therapeutic benefit. There is much discussion about the optimal approach for combining VNS and physical therapy, as such we sought to determine whether taVNS administered during robotic training, specifically delivered during the premotor planning stage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 48 publications
1
66
0
Order By: Relevance
“…The similar results are shown in other studies about non-invasive VNS. Transcutaneous auricular VNS, applied noninvasively to the peripheral auricular branch of the VS, can also improve the upper limb motor function of the patients suffered from cerebral I/R injury [ 36 38 ]. Furthermore, it has been suggested that sensor function can be significantly improved in chronic stroke patients following VNS treatment paired with the conventional rehabilitation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The similar results are shown in other studies about non-invasive VNS. Transcutaneous auricular VNS, applied noninvasively to the peripheral auricular branch of the VS, can also improve the upper limb motor function of the patients suffered from cerebral I/R injury [ 36 38 ]. Furthermore, it has been suggested that sensor function can be significantly improved in chronic stroke patients following VNS treatment paired with the conventional rehabilitation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (44) is the most recent study that evaluated the efficacy of the transcutaneous auricular VNS on the upper limb motor function. In this clinical trial, the authors included 34 patients with unilateral supratentorial chronic (>6 months) stroke.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The risk of bias assessment was applied to the six clinical trials (Dawson et (34,43,44,46,47,49) upon which the initial meta-analysis for the assessment of VNS efficacy for motor rehabilitation was based. All studies had low risk of bias in the selective reporting domain.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating clinical trials favoured VNS+Rehab for improving upper limb function in patients after a stroke 18–25. To date several meta-analyses have combined the effects of VNS+Rehab on upper limb function in patients who had a stroke and demonstrated that VNS might be beneficial for upper limb function recovery 26–28.…”
Section: Introductionmentioning
confidence: 99%